Origins of the Hawaiian flora: Phylogenies and biogeography reveal patterns of long‐distance dispersal. Issue 6 (9th December 2018) - Price, Jonathan P.; Wagner, Warren L.
Abstract: Botanists have long considered the origins of the Hawaiian flora in terms of long‐distance dispersal from particular source areas. We extensively reviewed phylogenetic studies of the Hawaiian angiosperm flora to determine the most likely region of origin for each lineage from a defined set of source areas. We also evaluated dispersal modes of each lineage to assess whether certain dispersal modes are associated with a given source area. The largest source category was Widespread (involving related taxa that extend across more than one region), although many of these comprised native non‐endemic species, and accounted for little of the total species diversity (after accounting for in situ speciation). The next largest source regions were Indo‐Malayan and Neotropical. Comparatively few lineages originated from the East Asian region, although these include the single largest lineage. Lineages originating in the Indo‐Malayan region predominantly arrived via Pacific Islands, whereas dispersal from all other regions appears to have been mostly direct. Compared with previous analyses, we found a higher proportion of lineages originating in the Neotropics and temperate North America. Widespread origins were positively associated with dispersal via flotation on water, whereas other origins were associated with dispersal by birds, either through internal transport or external adhesion. We identified thirty‐one potential cases of dispersal out of Hawaii to other islands. Our assessment is complicated by lineages with ancient origins, with further complications likely stemming from hybridization events. Overall, numerous lineages including some distinctive endemic genera have not had sufficient phylogenetic study to determine an origin.